(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Assinger, Philipp, Austria Carr, Deb, Australia D’Adamo-Weinstein, Lisa, United States Dolleman, Rusty, United States Hatch, Meredith, United States Kang, Dae Joong, South Korea Klein-Collins, Becky, United States Larusdottir, Fjola Maria, Iceland Nitardy, Charlotte, United States Rambharose, Rekha, South Africa Wanjiru, Catherine, Kenya Widger, Laura, Ireland